STRATEGI PENCEGAHAN PENYAKIT INEFEKSIUS PADA PETERNAKAN BROILER BERBASIS LABORATORIUM - Ardana, Ida Bagus Komang (Buletin Veteriner Udayana; Vol. 3 No. 1 Pebruari 2011)
Infectious diseases in broilers remain a problem caused huge economic losses in the form;performance (high mortality and mobidity, slow growth rate, bad feed conversion ratio(FCR), and low meat production), increaase medical costs, should performdecontamination (cleaning and disinfection) and revaccination. Failure on due to diseasethat occurs in broilers caused by the breeder has not completely make handling the diseaseis due to lack of management for prevention the disease. This paper proposed a strategy fordisease prevention by promoting bio-security measures, vaccination and medication-basedlaboratory. beternak ayam
Keywords: a strategy for disease prevention,vaccination and medication-based laboratory,